The pendulum-like fluxgate magnetic field sensor - Ubizskii, Sergii B.; Pavlyk, Lyubomyr P. (Sensors and actuators. A. Physical., 2008)
A fluxgate-type magnetic field transducer based on the ferromodulation effect is proposed in this work and named the pendulum-like fluxgate. It uses anharmonic torsion oscillations of magnetization direction in the homogeneously magnetized medium of a sensing element that are forced by the excitation field. To provide such mode of magnetization reversal the additional transversal bias field is used. Rotational magnetization is coherent with excitation field, reversible, without hysteresis and Barkhausen jumps. As a result it allows avoiding the main source of the traditional fluxgate noise and reducing essentially the sensitivity threshold. The mathematical model of device operation is build up for isotropic thin film core and the signal and spectrum characteristics are studied on this basis. The optimal conditions of magnetic field measurement are established from the point of view of the best sensitivity and lowest electrical power consumption as well as the way of avoidance of transversal sensitivity.